EDUKASI ISU LINGKUNGAN GLOBAL UNTUK SISWA SEKOLAH DASAR DI SD MUHAMMADIYAH 3 ICP SUMBERREJO - Laily Agustina Rahmawati; Joko Hadi Susilo; Nindy Callista Elvania; Ahmad Niamul Abrori; Winda Uswatun Khasanah (Universitas Kadiri, 2025)
Global environmental issue education at SDM 3 ICP Sumberrejo aims to improve elementary school students' understanding of global environmental issues, with the hope of creating environmental awareness that triggers pro-environmental actions. Educational activities consist of two stages, the first is by providing learning knowledge in class, the second is by using posters. Before the educational activities were held, many students still did not know about global environmental issues. Thus, students' awareness of the importance of the environment had not yet been formed and student actions that led to pro-environmental activities were still very rare. After the educational activities were held, the general conditions showed positive changes starting from increasing students' understanding of global environmental issues, school support to ensure the sustainability of the education process, and changes in student behavior towards being pro-environment. The success of the program is measured by increasing student understanding and changes in student behavior. Suggestions for increasing program effectiveness are by implementing environmental education regularly, implementing pro-environmental activities especially in commemoration of World Environment Day, and making school-university cooperation agreements for environmental assistance. This program makes an important contribution to efforts to foster environmental awareness from an early age in order to realize sustainable development.